Design problems with renovating and adapting an old mill on the example of the execution of an original project = Problemy projektowe związane z renowacją i adaptacją starego młyna na przykładzie autorskiej realizacji - Grzonka, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Nowadays, postindustrial areas and buildings are becoming more and more valuable. Very popular are those with special historical and architectural values, which are additionally located in large cities. The situation of those possessing fewer attributes encouraging their adaptation is worse. Sometimes, however, there are reasons why a decision is made to invest in such buildings despite the many difficulties connected with the implementation of these investments. This situation was presented on the example of the renovation and adaptation of an old electric mill in Łaziec into a restaurant.
Keywords: renowacja; adaptacja; modernizacja; obiekty poprzemysłowe; renovation; adaptation; modernization; postindustrial buildings